STEP inhibition reverses behavioral, electrophysiologic, and synaptic abnormalities in Fmr1 KO mice. (January 2018) - Chatterjee, Manavi; Kurup, Pradeep K.; Lundbye, Camilla J.; Hugger Toft, Anna Karina; Kwon, Jeemin; Benedict, Jessie; Kamceva, Marija; Banke, Tue G.; Lombroso, Paul J.
Abstract: Fragile X syndrome (FXS) is the leading cause of inherited intellectual disability, with additional symptoms including attention deficit and hyperactivity, anxiety, impulsivity, and repetitive movements or actions. The majority of FXS cases are attributed to a CGG expansion that leads to transcriptional silencing and diminished expression of fragile X mental retardation protein (FMRP). FMRP, an RNA binding protein, regulates the synthesis of dendritically-translated mRNAs by stalling ribosomal translation. Loss of FMRP leads to increased translation of some of these mRNAs, including the CNS-specific tyrosine phosphatase STEP (STriatal-Enriched protein tyrosine Phosphatase). Genetic reduction of STEP in Fmr1 KO mice have diminished audiogenic seizures and a reversal of social and non-social anxiety-related abnormalities. This study investigates whether a newly discovered STEP inhibitor (TC-2153) could attenuate the behavioral and synaptic abnormalities in Fmr1 KO mice. TC-2153 reversed audiogenic seizure incidences, reduced hyperactivity, normalized anxiety states, and increased sociability in Fmr1 KO mice. Moreover, TC-2153 reduced dendritic spine density and improved synaptic aberrations in Fmr1 KO neuronal cultures as well as in vivo . TC-2153 also reversed the mGluR-mediated exaggerated LTD in brain slices derived from Fmr1 KO mice. These studies suggest that STEP inhibition may have therapeutic benefit in FXS. Highlights: STEP inhibitor, TC-2153 rescues the core behavioral symptoms in FXS. STEP inhibition rescues the abnormalities in dendritic spines in FXS. STEP is involved in mGluR mediated exaggerated LTD in FXS.